THE DRAMATISATION OF LITERARY TEXTS AS A TOOL FOR FUTURE LANGUAGE STUDENTS TO MASTER THE IDIOMATIC ASPECTS OF LANGUAGE - Marat Galiullov (International Journal of Literature and Language Studies, 2026)
This article examines the potential of dramatising literary texts as a means for students of philology faculties to master the idiomatic aspects of a foreign language. It analyses the mechanisms for developing idiomatic competence through theatrical activities, the specific features of working with literary texts, and the impact of dramatisation on the development of students’ linguistic, communicative and interpretative competences.